Fluid transport : pipes - Duroudier, Jean-Paul (ISTE Press : Elsevier, 2016)
Fluid Transport: Pipes, part of the Industrial Equipment for Chemical Engineering set, provides a description and calculation of the essential equipment used for fluid transport. Gas-liquid flows are studied with regard to the nature of this type of flow, along with the pressure drop that they may trigger. Many numerical examples are offered, and the calculation of a fluid transport line is detailed. The vacuum technique and the behavior of non-Newtonian liquids is thoroughly presented, and the author also provides the methods needed for understanding the equipment used in applied thermodynamics to encourage students and engineers to self build the programs they need. Chapters are complemented with appendices that provide additional information and associated references.
Keywords: Gas distribution.; Gas-pipes.; elektronické knihy; electronic books